(untitled) (Atlas Journal of Biology, 2017)
Glycine max L. Merr., (soybean) is one of the major crops in the United States, south America and Asia. Yet, the seed yield of soybean is significantly reduced due to Heterodera glycines (Ichinohe), the soybean cyst nematode (SCN). SCN is one of the most destructive pests and pathogens of soybean because the main methods for control have proven difficult. Lineages of soybean that are resistant to SCN have been developed but it is yet unknown what all the molecular causes of this resistance are. Rhg1 and Rhg4 loci are two of about 10 loci that underlie resistance. The Rhg4 locus, is required for resistance to SCN race 3 in ‘Peking’–type derived resistances. One gene in the locus has been isolated and a causative link shown, but the surrounding regions have not been fully analyzed. Focusing on the Rhg4 locus, this study was aimed at uncovering other potential causes of resistance of soybean to SCN. In a bioinformatic analysis of the Rhg4 locus, alleles of nine genes were analyzed. The set of large intergenic regions have key regulatory elements in them. Since partial resistances are often multigeneic, some of these nine genes could be candidates for causing and regulating resistance.